Students’ Vocabulary Mastery Using Kahoot Platform Media - Fitri Rayani Siregar; Selvia Angela (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
The objective of the research is to examine the students’ vocabulary mastery by playing Kahoot platform media. A quantitative research was employed where the research involved 33 students as samples. The data was obtained through test from third semester students of undergraduate program English Education Department (TBI-2) Teacher Training Faculty IAIN Padangsidimpuan in 2019/ 2020 academic year. In sum, the students’ vocabulary mastery by using the application which names Kahoot platform media included into enough category by getting 43.82 score. The hypothesis formed was rejected based on the proof. Therefore, the students’ vocabulary mastery by using Kahoot platform media was not suitable with the researcher’s hope.